Delving into the dark ecology: A continent-wide assessment of patterns of composition in soil fungal communities from Australian tussock grasslands. (June 2019) - Egidi, Eleonora; Wood, Jennifer L.; Celestina, Corinne; May, Tom W.; Mele, Pauline; Edwards, Jacqueline; Powell, Jeff; Bissett, Andrew; Franks, Ashley E.
Abstract: Soil fungi play essential roles in many terrestrial processes, but our knowledge of the forces governing fungal distribution and community composition along broad-scale environmental gradients is still limited. In this study, we explored biogeographic distribution and composition of soil fungal communities associated with 62 tussock grasslands across different regions of Australia. Climatic parameters had only a limited correlation with fungal community structure, while edaphic variables and spatial distance were significantly associated with changes in fungal community composition. We also observed high variations in composition among fungal assemblages from different ecological regions, suggesting some regional endemism in these communities. The discrete distribution of fungi in soil was further confirmed by indicator analysis, which identified distinct indicator operational taxonomic units associated with grasslands from different climatic regions. Finally, fungi with flexible trophic interactions had a central role in the network architecture of both arid and temperate communities. Taken together, the results from our study confirm the prominent role of soil physico-chemical status and geographic location in determining fungal biogeographic patterns over large scales in Australia.